Perceived ease of use (PEOU) and perceived usefulness (PU) of information technology application towards managerial productivity in fast food chain outlets - Ngali, Norzaidah; Rahmat, Norazlina; Samsudin, Azlina; Abd Ghani, Fatimah; Hamid, Munirah; Ramli, Noorazlin; Md. Zaini, Zetty Madina; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
The usage of information technology in fast food chain outlets is to be pervasive and compulsory to improve organizational performance and strategic competitiveness. However, having technology available is not enough, it must be accepted and used appropriately by its target user group in order to realize anticipated productivity gains. Therefore, this study aims to examine the relationship between perceived ease of use (PEOU) and perceived usefulness (PU) of information technology application towards managerial productivity of managers who are attached in the fast food chain outlets in the Klang Valley area. A random survey with questionnaire method was conducted as a quantitative data collection on 326 managers from participating food chain outlets with regard to their acceptance of IT application leading to their productivity. The findings indicated that perceived usefulness (PU) have significant (positive) relationship on managerial productivity (MP). In contrast, ease of use (EOU) has insignificant (negative) relationship on MP. It has been concluded that perceived usefulness of IT application was influence the productivity of managers and on the other hand, the ease of use not influence manager's productivity in today's work environment. Based on the findings, it is hoped that this study will further enhance knowledge in the human resources field and training, with respect to managers' attitude and awareness towards IT application in restaurant operations.